Pomiar płynności rynku akcji na przykładzie GPW w Polsce - Milo, Władysław; Rutkowska, Magdalena; Materka, Rafał (Measurement of liquidity on the Warsaw Stock Exchange, 2006)
Market liquidity index is one of the most important indicators that describe states of capital markets. Investors prefer stocks with higher level of liquidity while they are subject to the less liquidity risk. Therefore market participants have then the greatest possibilities of using all investment strategies. Usually this means the possibility of quick purchase or sell of the stocks. In the article we present the alternative ways of measuring market liquidity. They enable further use of the obtained liquidity time series in forecasting and decision making.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 330-337